Detecting low frequency cycles in rainfall series from colombian coffee-growing area by using descriptive methods (2011)
Descriptive statistical methods were used for improving climatic variability scenarios regarding rainfall using time series from five representative pluviometric stations (Miguel Valencia, Naranjal, Cenicafé, La Bella and Paraguaicito); such scenarios are used to make decisions regarding coffee-growing. The purpose was to find signs of cyclic behaviour besides those associated with El Niño Southern Oscillation (ENSO) which happens every 3.5 to 4.5 years.  Signals were found of decadal to interdecadalcycle (10 to 30 years), modulating known ENSO effects related to periodic changes in the Pacific Ocean and solar activity.